Evolution and development of interhemispheric connections in the vertebrate forebrain - Suárez, Rodrigo; Gobius, Ilan; Richards, Linda J. (Frontiers in Human Neuroscience, 2014)
Axonal connections between the left and right sides of the brain are crucial for bilateral integration of lateralized sensory, motor and associative functions. Throughout vertebrate species, forebrain commissures share a conserved developmental plan, a similar position relative to each other within the brain and similar patterns of connectivity. However, major events in the evolution of the vertebrate brain, such as the expansion of the telencephalon in tetrapods and the origin of the six-layered isocortex in mammals, resulted in the emergence and diversification of new commissural routes. These new interhemispheric connections include the pallial commissure, which appeared in the ancestors of tetrapods and connects the left and right sides of the medial pallium (hippocampus in mammals), and the corpus callosum, which is exclusive to placental mammals and connects both isocortical hemispheres. A comparative analysis of commissural systems in vertebrates reveals that the emergence of new commissural routes may have involved co-option of developmental mechanisms and anatomical substrates of preexistent commissural pathways. One of the embryonic regions of interest for studying these processes is the commissural plate, a portion of the early telencephalic midline that provides molecular specification and a cellular scaffold for the development of commissural axons. Further investigations into these embryonic processes in carefully selected species will provide insights not only into the mechanisms driving commissural evolution, but also regarding more general biological problems such as the role of developmental plasticity in evolutionary change.